From mine to mind and mobiles – Lithium contamination and its risk management. (1st December 2021) - Bolan, Nanthi; Hoang, Son A.; Tanveer, Mohsin; Wang, Lei; Bolan, Shiv; Sooriyakumar, Prasanthi; Robinson, Brett; Wijesekara, Hasintha; Wijesooriya, Madhuni; Keerthanan, S.; Vithanage, Meththika; Markert, Bernd; et al.
Abstract: With the ever-increasing demand for lithium (Li) for portable energy storage devices, there is a global concern associated with environmental contamination of Li, via the production, use, and disposal of Li-containing products, including mobile phones and mood-stabilizing drugs. While geogenic Li is sparingly soluble, Li added to soil is one of the most mobile cations in soil, which can leach to groundwater and reach surface water through runoff. Lithium is readily taken up by plants and has relatively high plant accumulation coefficient, albeit the underlying mechanisms have not been well described. Therefore, soil contamination with Li could reach the food chain due to its mobility in surface- and ground-waters and uptake into plants. High environmental Li levels adversely affect the health of humans, animals, and plants. Lithium toxicity can be considerably managed through various remediation approaches such as immobilization using clay-like amendments and/or chelate-enhanced phytoremediation. This review integrates fundamental aspects of Li distribution and behaviour in terrestrial and aquatic environments in an effort to efficiently remediate Li-contaminated ecosystems. As research to date has not provided a clear picture of how the increased production and disposal of Li-based products adversely impact human and ecosystem health, there is an urgent need for further studies on this field. Graphical abstract: Image 1 Highlights: Biogeochemistry of Li influence bioavailability, toxicity, and remediation. High Li levels adversely affect human and ecosystem health. Li is readily taken up by plants and likely transferred into the food chain. An integrated risk management of Li contaminated environments is needed. Mechanisms and remediation possibilities of Li warrant further research.